Synthesis of new ferrocenyl dehydrozingerone derivatives and their effects on viability of PC12 cells. (15th October 2016) - Pedotti, Sonia; Patti, Angela; Dedola, Sonia; Barberis, Antonio; Fabbri, Davide; Dettori, Maria Antonietta; Serra, Pier Andrea; Delogu, Giovanna
Graphical abstract: The first monomer and biphenyl ferrocenyl derivatives of dehydrozingerone were prepared by straightforward methods, electrochemical effects were detected by cyclic voltammetry and significant increasing of the oxidative stress generated by hydrogen peroxide in PC12 cells was observed for some of them. Abstract: A series of novel compounds deriving from the conjugation of ferrocene with curcumin-related bioactive molecules as dehydrozingerone, zingerone and their biphenyl dimers was prepared by Claisen–Schmidt condensation of the suitable aromatic aldehydes and acetylferrocene in different conditions according to the starting material. The obtained compounds were fully characterized by NMR spectroscopy and cyclic voltammetry and reversible electrochemical behavior was recorded for monomer derivatives. The cell viability of PC12 cells after exposure to the organometallic compounds was also evaluated and a reduced toxicity with respect to the ferrocene was detected. In comparison with biphenyl4, a compound that manifested antiproliferative and apoptotic activities and was quite toxic on PC12 cells, the exposure to the ferrocenyl analogue14 resulted in roughly fourfold increase in the cell viability. Ferrocenyl chalcones14 and16 –18 significantly increased the oxidative stress generated by hydrogen peroxide, a molecule generally accumulated in cancer cells and, recently, studied as prodrug.